Do Tips Increase Workers' Income? - Shy, Oz (Management Science, 2015)
This paper constructs a model of service providers who compete in service and labor markets simultaneously to analyze the effects of tipping on hourly wages and total tip-inclusive hourly worker compensation. An increase in the tipping rate reduces hourly wages. Total worker compensation increases at different rates depending on the market structure, market coverage, and employment level, with the exception of price-taking (competitive) service providers, where the tip-inclusive hourly income declines with the tipping rate. The paper develops an index of “effective tipping” that measures the net percentage change in total hourly worker compensation associated with each tipping rate. This paper was accepted by John List, behavioral economics.